Impacts of dam construction on mercury methylation and bioaccumulation revealed by stable isotopes - Kim, Young-Gwang; Yoon, Ji Won; Kang, Sujin; Shin, Kyung-Hoon; Hyun, Jung-Ho; Ra, Kongtae; Kim, Jung-Hyun; Kwon, Sae Yun (Environmental pollution (1987), 2025)
Impacts of dam construction on mercury (Hg) sources, biogeochemical cycling, and bioaccumulation were investigated along the west coast of Korea, where large-scale national projects were initiated between 1978 and 1990 to build dam or weir at the interface between rivers and estuaries. Total Hg (THg) and methylmercury (MeHg) concentrations and Hg stable isotopes in estuarine sediment cores sampled downstream of dam/weir reveal 74 ± 3% reduction in THg, 536 ± 158% increase in MeHg, and shifts in Hg sources from riverine export to wet deposition (precipitation) as revealed by increases in Δ199Hg (by 0.13 ± 0.03‰) and Δ200Hg (by 0.10 ± 0.01‰). Stable carbon isotopes, n-alkanes, and four geochemical pools of Hg extracted from the sediment cores show enhanced proportion of labile (F1; 0.28 ± 0.21% points) and organically-bound (F2; 34 ± 12% points) Hg fractions and the ratio of marine-based organic matter relative to recalcitrant Hg bound to terrestrial organic matter at the downstream estuary. Dam/weir constructions have significant effects on Hg bioavailability and methylation, by enhancing the proportion of dissolved Hg delivered by precipitation and those subject to efficient assimilation by marine algae and microbial utilization. This is evident by the negative δ202Hg shifts in the sediment cores at the depths of MeHg peaks. Cessation of riverine Hg input is manifested by 96% reduction of THg in shellfish and enhanced methylation appears to cause 106% increase in fish THg at the downstream estuarine ecosystem. This study underscores the importance of considering complex and long-term biogeochemical modifications as a part of Environmental Impact Assessments. [Display omitted] •Estuarine dam construction increases dissolved Hg input from the atmosphere.•There is also an increase in the proportion of Hg bound to marine organic matter.•Enhanced Hg bioavailability leads to methyl Hg production in downstream estuaries.•Shellfish and fish display 96% reduction and 106% increase in Hg, respectively.